Fractionation and fluxes of metals and radionuclides during the recycling process of phosphogypsum wastes applied to mineral CO2 sequestration. (November 2015) - Contreras, M.; Pérez-López, R.; Gázquez, M.J.; Morales-Flórez, V.; Santos, A.; Esquivias, L.; Bolívar, J.P.
Highlights: An environmental proposal for wastes management is proposed. A process of CO2 mineral sequestration using phosphogypsum waste and soda is reported. Very high efficiencies of carbon sequestration are achieved under ambient conditions. Metals and radionuclides are released from phosphogypsum and fixed in final calcite. Abstract: The industry of phosphoric acid produces a calcium-rich by-product known as phosphogypsum, which is usually stored in large stacks of millions of tons. Up to now, no commercial application has been widely implemented for its reuse because of the significant presence of potentially toxic contaminants. This work confirmed that up to 96% of the calcium of phosphogypsum could be recycled for CO2 mineral sequestration by a simple two-step process: alkaline dissolution and aqueous carbonation, under ambient pressure and temperature. This CO2 sequestration process based on recycling phosphogypsum wastes would help to mitigate greenhouse gasses emissions. Yet this work goes beyond the validation of the sequestration procedure; it tracks the contaminants, such as trace metals or radionuclides, during the recycling process in the phosphogypsum. Thus, most of the contaminants were transferred from raw phosphogypsum to portlandite, obtained by dissolution of the phosphogypsum in soda, and from portlandite to calcite during aqueous carbonation. These findings provide valuable information for managing phosphogypsum wastes and designing potential technological applications of the by-products of this environmentally–friendly proposal.